Effect of Employee Competency on Employee Performance Moderated by Organizational Community - Roviana, Rina; Bahiroh, Eloh; Zarkasyi, Ali Imron; Amiruddin, Amiruddin (Journal of Business Management and Economic Development, 2025)
The purpose of this study was to ascertain how employee competence at Ramayana Mall Serang affected employee performance, which was influenced by organizational commitment. This study employs a descriptive methodology and a quantitative research design. Next, the study's population, which consists of 67 respondents, is the staff of Ramayana Mall Serang. Using non-probability sampling approaches, this study intends to examine and ascertain the impact of employee competence (X) on employee performance (Y), which is then regulated by organizational commitment (Z) at Ramayana Mall. Using the SmartPLS4.0 analysis tool, structural equation modeling, or SEM, is the data analysis method employed in this thesis study. According to the study's findings, (1) employee performance is positively and significantly impacted by employee competency. (2) Employee performance is positively and significantly impacted by organizational commitment. (3) The relationship between employee competency and performance is not moderated by organizational commitment in a positive and meaningful way.